Spiegare e argomentare la risposta.
f''(x)=- 12·x
f'(x)=
∫ - 12·x dx= - 6·x^2 + a
f(x)=
∫(- 6·x^2 + a) dx = a·x - 2·x^3 + b
f'(-1)=-3:
- 6·(-1)^2 + a = -3---> a - 6 = -3---> a = 3
f(x)=3·x - 2·x^3 + b
∫(3·x - 2·x^3 + b) dx =
=- x^4/2 + 3·x^2/2 + b·x + c
valutato in x = 2:
- 2^4/2 + 3·2^2/2 + b·2 + c= 2·b + c - 2
valutato in x = -1:
- (-1)^4/2 + 3·(-1)^2/2 + b·(-1) + c=
=-b + c + 1
Deve essere:
2·b + c - 2 - (-b + c + 1) = 3·b - 3
3·b - 3 = -18---> b = -5
quindi la funzione f(x):
f(x)= - 2·x^3 + 3·x - 5